2015
DOI: 10.1111/jsap.12370
|View full text |Cite|
|
Sign up to set email alerts
|

Coagulation status in dogs with naturally occurring Angiostrongylus vasorum infection

Abstract: OBJECTIVES Angiostrongylus vasorum infection is associated with bleeding tendencies in approximately one‐third of clinical cases. The cause of the coagulopathy is poorly understood but may be related to disseminated intravascular coagulation. Thromboelastography is a global evaluation of coagulation and has not been described in a cohort of dogs with this disease. MATERIALS AND METHODS Thromboelastography in association with other measures of coagulation including prothrombin and activated partial thromboplast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
115
2
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 43 publications
(120 citation statements)
references
References 21 publications
2
115
2
1
Order By: Relevance
“…So far, hyperfibrinolysis has been described in one dog with A. vasorum infection using thromboelastography (TEG) (Schmitz and Moritz, 2009). A recent study reported TEG results in 30 dogs, however, this study did not conclusively prove the presence of hyperfibrinolysis (Adamantos et al, 2015). At any rate, in view of quite variable results of platelet numbers, coagulation times, fibrinogen and D-Dimer concentrations in dogs bleeding due to A. vasorum infection, various mechanisms, including iatrogenic actions, probably play a pathogenetic role.…”
Section: Discussionmentioning
confidence: 57%
See 4 more Smart Citations
“…So far, hyperfibrinolysis has been described in one dog with A. vasorum infection using thromboelastography (TEG) (Schmitz and Moritz, 2009). A recent study reported TEG results in 30 dogs, however, this study did not conclusively prove the presence of hyperfibrinolysis (Adamantos et al, 2015). At any rate, in view of quite variable results of platelet numbers, coagulation times, fibrinogen and D-Dimer concentrations in dogs bleeding due to A. vasorum infection, various mechanisms, including iatrogenic actions, probably play a pathogenetic role.…”
Section: Discussionmentioning
confidence: 57%
“…Furthermore, coagulation times are usually normal, in experimentally as well as naturally infected dogs , Borgeat et al, 2015Matos et al, 2016). In contrast, another subgroup of dogs mainly presents with clinical signs dominated by bleeding and, like in our case series, abnormal coagulation tests are usually present (Chapman et al, 2004, Adamantos et al, 2015.…”
Section: Discussionmentioning
confidence: 78%
See 3 more Smart Citations